Image Processing of Antibody Detection using Machine Learning for an Optical Bio-sensing Application - Tieppo, Bianca; Vale, Daniella L.; Fonsaca, Jéssica E.S.; Rehan, Mohd; Megid, Jane [UNESP]; Teixeira, Wanderson S.R. [UNESP]; Grasseschi, Daniel; de Matos, Christiano J.S.; Saito, Lúcia A.M. (Optica Publishing Group, 2023)
We propose images processing recorded with a waveguide sensor of an immunological test based on antigen-antibody reaction. Machine Learning combining optical detection identifies bovine brucellosis antibodies and can be useful for other immunoassays.